Preface: 3rd International Conference on Advances in Materials, Machinery, Electrical Engineering (AMMEE 2024) - Zhong, Jiayi; Sikora, Axel (Transactions on Engineering and Technology Research, 2024)
The 3rd International Conference on Advances in Materials, Machinery, Electrical Engineering (AMMEE 2024) held at the city of Tianjin, China, during June 29-30, 2024, and provides two days' focus on the science and technology that are the basis for mechanical engineering and industrial informatics. The theme of the plenary session is “Materials, Machinery, Electrical Engineering” featuring invited speakers who will further explore this topic that is so significant for materials, machinery, electrical engineering. Concurrent sessions and a poster session will cover a wide range of topics and issues, including both contributed papers and special sessions developed on specific themes, all with a central focus of materials, machinery, electrical engineering.This 3rd AMMEE received a total of 71 submissions. And more than 20 submissions have been accepted by our reviewers. By submitting a paper to this AMMEE conference, the authors agree to the review process and understand that papers undergo a peer-review process. Manuscripts will be reviewed by appropriately qualified experts in the field selected by the conference committee, who will give detailed comments and-if the submission gets accepted-the authors submit a revised version that takes into account this feedback. All papers are reviewed using a double-blind review process: authors declare their names and affiliations in the manuscript for the reviewers to see, but reviewers do not know each other's identities, nor do the authors receive information about who has reviewed their manuscript.We would like to express their sincere appreciation and thanks to all the members of the AMMEE 2024 Conference Technical Program Committee for their tremendous efforts. They are indebted to the referees for their constructive comments on the papers. Without their dedication, it was impossible to have a successful AMMEE 2024 and a high quality volume of the conference proceedings.Jiayi Zhong and Axel SikoraConference Organizing CommitteeTianjin, China